2020
DOI: 10.3389/fchem.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of the Palladium-Catalyzed 3-Butene-2-ol Amination Reaction: A DFT Study

Abstract: Palladium-catalyzed asymmetric allylic substitution, due to its valuable reactive profile, has become a quite useful tool in organic synthesis fields. In the present study, density functional theory (DFT) calculations were applied to investigate the important factors for palladium-catalyzed 3-butene-2-ol and methylaniline amination reaction, with tetrahydrofuran (THF) as solvent. We find that this catalytic protocol results in high regio-and stereoselectivity, which is in line with the experimental result. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[76] In 2020, Huang and co-workers utilized DFT calculations to investigate the mechanism underlying the palladium-catalysed amination of 3-buten-2-ol and methylaniline, providing insights into the critical factors affecting this reaction (Figure 24). [77] It was found that ammonium A obtained through the reaction between methylaniline and allylicpalladium species plays a crucial role in CÀ O bond activation of allyl alcohol. Meanwhile, steric hindrance between the substrate and the ligands on the catalyst is responsible for regioselectivity and stereoselectivity.…”
Section: Pd-catalysed Cà O Activationmentioning
confidence: 99%
“…[76] In 2020, Huang and co-workers utilized DFT calculations to investigate the mechanism underlying the palladium-catalysed amination of 3-buten-2-ol and methylaniline, providing insights into the critical factors affecting this reaction (Figure 24). [77] It was found that ammonium A obtained through the reaction between methylaniline and allylicpalladium species plays a crucial role in CÀ O bond activation of allyl alcohol. Meanwhile, steric hindrance between the substrate and the ligands on the catalyst is responsible for regioselectivity and stereoselectivity.…”
Section: Pd-catalysed Cà O Activationmentioning
confidence: 99%
“…In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported [25–28] . Zheng and co‐workers [26] studied Ir catalyzed α‐amidation of 2‐acylimidazoles and demonstrated a significant effect of nitrene insertion.…”
Section: Introductionmentioning
confidence: 97%
“…Sunoj et al [27] investigated the mechanistic insights into asymmetric amination of diazoacetate catalyzed by dirhodium tetra(trifluoro)acetate with chiral SPINOL-phosphoric acid and found a stereo-controlling transition state with cooperative participation of both catalysts. Huang and Liu [28] explored a palladium-catalyzed 3-butene-2-ol and methyl aniline amination reaction and found that the high regio-and stereoselectivity is caused by the steric hindrance between the substrate and the catalyst ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation